A formação dos coordenadores pedagógicos da Semed-Maceió: 2012-2013 - Ciriaco, Marise Leão (2015)
This research aims at analyzing the continuing professional development projects of pedagogical coordinators of the Municipal Secretariat of Education of Maceió (Semed-Maceió). Focused on the qualitative analysis, this study uses as document analysis data collection technique that includes: the Internal Regulations of Semed- Maceió; the references for teacher professional development; and the continuing education projects of the pedagogical coordinators, in the 2012-2013 period, from the elementary school of the Municipal Public Education System of Maceió. The referred continuing education projects are related to what is described in the following: the documents; the theoretical-practical implementation process; and the impact of the coordinator s performance as a teacher developer, identifying both the limits and possibilities of the coordinator/developer work in fostering teacher development. The syllabi analysis of the teacher development projects of Semed-Maceió enabled us to infer that the absence of specific curriculum guidelines meeting the required profile to this professional contributes to the precariousness of performing the coordination function, mainly concerning the curriculum guidance of the pedagogical coordinator as a teacher developer, given he/she is not provided with theoretical-methodological subsidies which enable not only the construction of a macro view of the teacher development process, but the systematization of his/her action as well, with the development of a definition of teacher performance indicators who are in the process of continuing education. The theoretical framework of this study is based on Tardif & Garcia s concepts, contributing to establishing a dialogue between the research objectives and the synthesis of the analyzed documents. The findings may contribute to further reflection on the importance of the teacher developer education process as well as for re-dimensioning the teacher development elementary school project recommended by Semed-Maceió